Factores que afectan la germinacion de Justicia squarrosa Griseb, forrajera nativa de la region chaqueña de la Argentina - Zalazar, M.=700 1 Funes, G.; Venier, M.P.
(Es, En)
Ilus., 31 ref.
Keywords: JUSTICIA; GERMINACION; TEMPERATURA; LUZ; ESTRES; LONGEVIDAD; SEMILLAS; ARGENTINA; JUSTICIA SQUARROSA; AGRISCIENTIA